ANALISIS PERBANDINGAN KINERJA KANTOR SAMSAT UPTD WILAYAH IV BIREUEN DAN UPTD WILAYAH IV LHOKSEUMAWE - Yusri, Yusri; Konadi, Win (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2023)
This research aims to determine the performance of UPTD Samsat Region IV Bireuen and Region V Lhokseumawe City based on the realization of Motor Vehicle Tax (PKB) collection, Motor Vehicle Transfer of Title Fee (BBN-KB) services. Analysis was carried out using independent two mean test statistics with t-statistics. The research results show that; A). The performance level of Samsat UPTD Region IV Bireuen in terms of the PKB Realization aspect during 2010 - 2021 is on average better than the performance level of UPTD Samsat Region V Lhokseumawe. B). The performance level of UPTD Samsat Region IV Bireuen from the aspect of BBN-KB Realization during 2010 - 2021 is also better on average, although not significantly different from the performance level of UPTD Samsat Region V Lhokseumawe. C). The diversity of PKB and BBN-KB income at the Samsat IV Bireuen office varies more between years than at Samsat V Lhokseumawe